COMMUNICATIVE COMPETENCE AS A BASIS FOR SUCCESSFUL IMPLEMENTATION OF INTERNATIONAL PROJECTS - Tsaryk, Olga (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to the study of communicative competence as a basis for the successful implementation of international projects. The concepts of "competence" and "communicative competence" are considered. The purpose of the article is to analyze the main methods and forms of development of communicative competence, the study of communicative competence as a basis for the successful implementation of international projects. It was established that communicative competence is defined as an integrative personal resource that ensures the success of communicative activity. The development of communicative competence includes the organization of communication, the development of communicative abilities and the formation of communicative skills. It has been proven that communicative competence can be effectively developed with the help of international projects. The priority task of the university is the development and implementation of international projects and programs in the field of youth work. It is emphasized that improvement of communicative competence cannot be separated from personality development. Keywords: competence, communicative competence, project method, international project.